Research advances and challenges in biogeotechnologies - He, Jia (2019)
In recent years, there has been a surge in the study of applying biotechnologies to geotechnical engineering by using microbial processes to change the physical and mechanical behaviour of soils and rocks. Methods based on this approach have been named biogeotechnologies. An overview of the research and development activities in this area in the past years is presented in this paper. The microbial effects that can be utilised in geotechnical engineering involve biocement, microbial desaturation, biofilm and so on. The applications of biogeotechnologies involve soil strengthening, seepage control, mitigation of soil liquefaction, soil erosion control, remediation of contaminated ground and so on. Problems and challenges related to methods for field implementation, monitoring and investigation techniques and environmental impacts are also discussed in this paper.